Identifying The Work Motivational Factors In NGOs For Millennials & Generation Z (Study Case: Five NGO’S In Bandung) - Sopana, Wijang Praba; Pritasari, Adita (Journal of Business and Management, 2020)
Motivation for someone to work is to obtain financial benefits, while people that working in NGOs should have social factors as their main motivation. Nowadays is the time for millennials and generation z to work. Millennials and generation z’s are the generation that has a lower social concern than the previous generation and is also a generation that that considers that profits are measured by financial measures. The reality is that at present, in Indonesia the number of NGOs and NGO members from the millennial generation continues to grow. The results are two contradictory matters. Therefore, this research tries to identify the determinants of work motivation for NGO workers in Bandung. Some selected NGOs are Environment, Law and Legal, Child Care, Health, and Social Entrepreneur NGOs. Data were collected by quantitative methods through a survey method by questionnaire and the result was proceeded by using factor analysis method to find the most dominant factor. Motivation factors for NGO workers are obtained from various experts and summarized into Self-Development, Self-Satisfaction, Humanitarian, Social Relations, Work Security, and Reward. After doing the analysis factor process and labeling for each new factor, five new factors emerge, namely rewards and work benefit, internal-orientation, development in self and society, external-orientation, and self-actualization and the main motivational factor is the reward and work benefits, and this was different from the first hypothesis that is due to social factors. This research will be useful for NGOs as data to make decisions about work motivation issues for millennials and generation z’s to improve performance and reduce turnover.